Olfactory Performance as an Indicator for Protective Treatment Effects in an Animal Model of Neurodegeneration - Meyer, Anja; Gläser, Anne; Bräuer, Anja U.; Wree, Andreas; Strotmann, Jörg; Rolfs, Arndt; Witt, Martin (Frontiers in Integrative Neuroscience, 2018)
Background: Neurodegenerative diseases are often accompanied by olfactory deficits. Here we use a rare neurovisceral lipid storage disorder, Niemann-Pick disease C1 (NPC1), to illustrate disease-specific dynamics of olfactory dysfunction and its reaction upon therapy. Previous findings in a transgenic mouse model (NPC1-/-) showed severe morphological and electrophysiological alterations of the olfactory epithelium (OE) and the olfactory bulb (OB) that ameliorated under therapy with combined 2-hydroxypropyl-ß-cyclodextrin (HPßCD)/allopregnanolone/miglustat or HPßCD alone. Methods: A buried pellet test was conducted to assess olfactory performance. qPCR for olfactory key markers and several olfactory receptors was applied to determine if their expression was changed under treatment conditions. In order to investigate the cell dynamics of the OB, we determined proliferative and apoptotic activities using a bromodeoxyuridine (BrdU) protocol and caspase-3 (cas-3) activity. Further, we performed immunohistochemistry and western blotting for microglia (Iba1), astroglia (GFAP) and tyrosine hydroxylase (TH). Results: The buried pellet test revealed a significant olfactory deterioration in NPC1-/- mice, which reverted to normal levels after treatment. At the OE level, mRNA for olfactory markers showed no changes; the mRNA level of classical olfactory receptor (ORs) was unaltered, that of unique ORs was reduced. In the OB of untreated NPC1-/- mice, BrdU and cas-3 data showed increased proliferation and apoptotic activity, respectively. At the protein level, Iba1 and GFAP in the OB indicated increased microgliosis and astrogliosis, which was prevented by treatment. Conclusions: Due to the unique plasticity especially of peripheral olfactory components the results show a successful treatment in NPC1 condition with respect to normalization of olfaction. Unchanged mRNA levels for olfactory marker protein and distinct olfactory receptors indicate no effects in the OE in NPC1-/- mice. Olfactory deficits are thus likely due to central deficits at the level of the OB. Further studies are needed to examine if olfactory performance can also be changed at a later onset and interrupted treatment of the disease. Taken together, our results demonstrate that olfactory testing in patients with NPC1 may be successfully used as a biomarker during the monitoring of the treatment.